Adapted Dance Improves Motor Abilities and Participation in Children With Down Syndrome: A Pilot Study. Issue 1 (January 2019) - McGuire, Michelle; Long, Jason; Esbensen, Anna J.; Bailes, Amy F.
Abstract : Purpose: This pilot study measured effects of an adapted dance program on motor abilities and participation in children with Down syndrome (DS) and explored caregivers' qualitative feedback regarding its benefits. Methods: Children with DS participated in 20 weekly 1-hour adapted dance sessions. The Canadian Occupational Performance Measure (COPM) and Gross Motor Function Measure (GMFM) Dimensions D and E were administered before and after the program. Caregivers completed a survey at the last session. Results: Six children completed pre- and postassessments. Significant improvements were noted in GMFM-88 measures. Caregivers of 5 participants reported improved scores on the COPM that were not significant. Caregivers reported physical, cognitive, and emotional improvements. Conclusions: This study supports use of an adapted dance program to improve motor abilities and participation in children with DS. Video Abstract: For more insights from the authors, access Supplemental Digital Content 1, available at:http://links.lww.com/PPT/A231 . Abstract : Supplemental Digital Content is Available in the Text.This pilot study measured effects of an adapted dance program on motor abilities and participation in children with Down syndrome and explored caregivers' qualitative feedback regarding its benefits.